Negotiating Religious Beliefs in a Medical Setting - Cordella, Marisa (Journal of religion and health, 2012)
This manuscript studies in detail, following a discourse analytical approach, medical consultations in which a patient's religious belief does not allow blood transfusion to be administered. The patient is a young Jehovah's Witness suffering myeloid leukaemia who is being treated in a Catholic cancer hospital where the practice of blood transfusion forms part of the standard protocol to treat the disease. The consultations under analysis take place in a Chilean cancer clinic where mainly the oncologist and a Jehovah's Witness Representative (JWR) present discuss and negotiate expert information on the substitute methods to be used. The exchange dynamics of the consultations differ from the usual visits where the medical knowledge and expertise is primarily in the hands of the medical practitioner. In these encounters, the JWR shares vital information with the oncologist providing the basis of the treatment to be used. This shifting of the balance of powerwhich could have been a cause of tension in the visit and a contributing factor in the disruption of communicationhas instead brought light to the encounter where the negotiated treatment has been achieved with relative ease. The patient's future is in the hands of the oncologist and the JWR, and their successful negotiation of treatment has made it possible to cater for the particular needs of a JW patient. Sharing different medical practices has not been an obstacle, but an opportunity to find out ways to deliver equity access and well-informed practices to a non-conventional patient.